Eksplorasi Profitabilitas, Likuiditatas, Rasio Leverage, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Textile dan Garmen yang Terdaftar di BEI Periode Triwulan (2019-2024) - Rahayu Nur Azizah; Ariati Anomsari; Maria Safitri; Fakhmi Zakaria (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study was conducted due to fluctuations in the market value of companies in the textile and garment industries on the Indonesia Stock Exchange, which are influenced by financial performance. The research question is whether Profitability, Liquidity, Leverage Ratio, and Firm Size affect Market Value. The objective of this study is on analyze the partial effects of these four factors on market value during the 2019- 2024 period. The study population consists of 23 textile and garmen listed on the IDX during the 2019- 2024 period. The sampling method used is purposive sampling, with a sample size of 17 companies. This study employs a quantitative approach using panel regression, and data analysis was conducted using Eviews version 13. The results indicate that Profitability has significant positive effect on Firm Value, whereas Liquidity and Firm Size do not have a significant effect on Firm Value. Conversely, the Leverage Ratio has a significant negative effect on Firm Value.